Risk evaluation in information technology assets in a MIPYME (SCIÉNDO INGENIUM, 2022)
This research goal was evaluating the risk in the information technology assets in a MiPyme using an evaluation model based on good practices. The research is descriptive, and the proposed model was validated using the expert judgement method with the Kendall's concordance coefficient W and the Chi-square test. As a result, we proposed an information technology asset risk evaluation model using components of the methodologies MAGERIT and OCTAVE-S, and the international standards ISO 27005 and ISO 31000. The model was validated and successfully applied to an urban transportation MiPyme of Trujillo province, there were identified 19 critical assets which allowed to identify 248 potential asset risks of which 06 are not acceptable, for which 02 risk treatment plans were proposed.
Keywords: Risk evaluation; information technology assets; MiPyme